Pengaruh Pengetahuan Merek, Hubungan Merek, Familiaritas Merek, Kepercayaan Merek Dan Fit Merek Terhadap Minat Beli Air Mineral Aqua - Ronny Reginaldo dan Chairy (Universitas Tarumanagara, 2019)
This study aims to determine the influence of brand knowledge, brand relationships, brand familiarity, brand trust, brand fit and purchase intention on Air Mineral Aqua. There are five variables of brand knowledge, brand relationship, brand familiarity, brand trust, brand fit as independent variable and purchase intention as dependent variable. The samples in this research is Aqua mineral water consumer in Jakarta. Samples were taken based on sampling method. This study examines 150 respondents. The method of analysis using multiple regression analysis method, classical assumption test and hypothesis test such as t test, F test, and coefficient of determination or R square. Tests in this study using SPSS software version 23. There are some results,. Based on the t test statistic test, brand knowledge, brand relationships, brand familiarity and brand trust have a significant influence on purchase intention with a significance value of less than 0.05, but the brand fit has no significant effect on purchase intention with a significance value of more than 0.05. Meanwhile, based on F test statistical tests indicate that brand knowledge, brand relationships, brand familiarity, brand trust and brand fit simultaneously affect purchase intention. The results of the coefficient of determination indicate that brand knowledge, brand relationships, brand familiarity, brand trust and brand fit are able to explain 26.50% of purchase intention. While the rest of 73.50% is explained by other variables outside of the study.